2015
DOI: 10.1016/j.jcct.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, multicenter, multivendor study of myocardial perfusion imaging with regadenoson CT perfusion vs single photon emission CT

Abstract: This study establishes the noninferiority of regadenoson CTP to SPECT for detecting or excluding myocardial ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 34 publications
0
45
1
Order By: Relevance
“…Cury et al (45) performed another multicenter trial using different vendor scanners (64, 128, 256 or 320 detector row). They enrolled 110 patients with suspected or known CAD, and also regadenoson was used as stress agent.…”
Section: Clinical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Cury et al (45) performed another multicenter trial using different vendor scanners (64, 128, 256 or 320 detector row). They enrolled 110 patients with suspected or known CAD, and also regadenoson was used as stress agent.…”
Section: Clinical Evidencementioning
confidence: 99%
“…Most of these were performed in a limited number of patients and using different scanner generations, showing high sensitivity and negative predictive value, and moderate specificity and positive predictive value. Newer single center studies have shown improved positive predictive value as well as specificity, being validated by two large multicenter trials (43)(44)(45)(46).…”
Section: Introductionmentioning
confidence: 99%
“…54 There are extensive CTP data favorably comparing its accuracy to ICA, MPI, and stress MRI for the detection of >50% stenosis by ICA. [55][56][57][58] The ability to reduce false-positive findings by discounting perfusion abnormalities in the distribution of normal vessels offers an advantage over the other functional tests, all of which lack an anatomic component. There are several studies comparing CTP with invasive FFR (Table 4).…”
Section: Ct Myocardial Perfusion Imagingmentioning
confidence: 99%
“…[92][93][94] CT perfusion may improve the overall diagnostic accuracy of cardiac CT, particularly in the interpretation of intermediate (30-70%) stenosis, 95 in the evaluation of stent patency, 96 and of diffuse atherosclerotic involvement with densely calcified plaques 97 ( Figure 5). …”
Section: Plaque Features Associated With Vulnerabilitymentioning
confidence: 99%